PENAMBAHAN BERBAGAI PERISA DAN BAHAN CAMPURAN TERHADAP PREFERENSI KONSUMEN PADA SOSIS BELUT (Monopterus albus) - Rossi, Evy; Herawati, Netti; ', Suntoro (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this study was to determine the effect of a variety of seasioning and seasioning mixed materials to test consumer preferences in eel sausages (Monopterus albus). This research was carried out experiments using nine treatments, which consists of: K1: basic formulation, K2: The addition of carrageenan 1% + 1% barbeque seasioning. (w/w), K3: The addition of carrageenan 1% + 1% curry seasioning. (w/w), K4: The addition of carrot flour 1.5% + 1% barbeque seasioning. (w/w), K5: The addition of flour carrot curry seasioning 1.5% + 1%. (w/w), K6: The addition of egg yolks 2% + barbeque seasioning 1%. (w/w), K7: The addition of 2% egg yolks  + 1% curry seasioning. (w/w), K8: The addition of 1.5% oyster mushrooms + 1% barbeque seasioning. (w/w), and K9: The addition of 1.5% oyster mushroom + 1% curry seasioning. (w/w). Data were analyzed statistically by using a Preference Test Mapping with assistance XL STAT software version 2013. Test hedonic and descriptive analyzed using PCA (Principal Component Analysis). Agglomerative hierarchical clustering (AHC) was used to see all grades of eel sausage. Based on the descriptive analysis using PCA and hedonic analysis using the AHC showed that treatment K2 (addition of 1% carrageenan seasioning barbeque + 1%) and treatment of K4 (addition of carrot flour 1.5% + 1% seasioning barbeque) were expressed panelists who liked their color. Preference Mapping analysis results showed that the treatment K2 (addition of 1% carrageenan + barbeque  seasioning 1%) and treatment of K4 (addition of 1.5% carrot flour + 1% barbeque seasioning) was the best treatment with the ability to be Able to explain the diversity of the data is by 80-100%.   Keywords : Eel, sausage, carrageenan, curry seasioning, barbeque seasioning, AHC,   PCA, Preference Mapping.